If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ax + -1r = 12 Solving ax + -1r = 12 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'r' to each side of the equation. ax + -1r + r = 12 + r Combine like terms: -1r + r = 0 ax + 0 = 12 + r ax = 12 + r Divide each side by 'x'. a = 12x-1 + rx-1 Simplifying a = 12x-1 + rx-1 Reorder the terms: a = rx-1 + 12x-1
| 4(6p-8)=24p-23 | | 15r=60 | | 43z-1=4(13z-16) | | -10x+9x=-9+10 | | 1.43x(-19/37)= | | -4z-4z=3z+3+3z | | 30-10k=22-2k | | 7=12z+18-5 | | Y=yz+10 | | -8(-8x-6)=-6x-222 | | s+7(4)=16 | | 193=3+10p | | -3(-3+y)+3y=4 | | -5m=-85 | | -7(x+4)=0 | | 6n-2(3-n)=-13 | | 44+2c=7c-6 | | x/13=-7 | | 3x+3/3= | | 6(2m-1)-1(11m+6)=7 | | 7x-11=17-7x | | 60-2m=8m | | 7+14=16 | | 6x-7+3x=10+9x-7 | | 13=3x-6 | | 3-10+1-5= | | y=z+x-8/w | | 14=p/2 | | 4z=2.5+2.7 | | 27=0.5x(2+7) | | 9-1/2b=5+8/2b | | xx=42 |